PENDAMPINGAN BRANDING DAN MARKETPLACE UMKM KERIPIK TEMPE DAN PISANG DI DESA NAMPAN KECAMATAN SUKOREJO KABUPATEN PONOROGO - Suyoto Arief; Ramdani Harahap, Soritua Ahmad; Elang Bintang; Aisy, Muwatsiqul; Nur Briyan (LPPM STAIMAS WONOGIRI, 2024)
MSMEs are a source of income for rural communities. Development and management are needed in running MSMEs. MSMEs (Micro, Small and Medium Enterprises) are independent production sectors managed by the private sector or legal entities in all economic sectors, however, there are still a few from the village community who do not understand how to develop and manage MSMEs. Where the MSMEs they have are very feasible and good to be marketed widely, as in one of the communities in Nampan Ponorogo Village, East Java, Mrs. Anna's MSMEs are tempe and banana chips. Therefore, this activity aims to provide assistance and understanding regarding how to develop and manage MSMEs so that these business activities can grow and develop and be able to compete with products in the market today. The method used in community service activities (PkM) by applying